Economic evaluation of a randomized controlled trial of an intervention to reduce office workers’ sitting time: The"Stand up Victoria" trial - Gao, L.; Flego, A.; Dunstan, D.; Winkler, E.; Healy, Genevieve; Eakin, E.; Willenberg, L.; Owen, N.; Lamontagne, A.; Lal, A.; Wiesner, G.; Hadgraft, N.; et al. (Tyoterveyslaitos, 2018)
© 2018, Nordic Association of Occupational Safety and Health. All rights reserved. Objectives This study aimed to assess the economic credentials of a workplace-delivered intervention to reduce sitting time among desk-based workers. Methods We performed within-trial cost-efficacy analysis and long-term cost-effectiveness analysis (CEA) and recruited 231 desk-based workers, aged 24–65 years, across 14 worksites of one organization. Multicomponent workplace-delivered intervention was compared to usual practice. Main outcome measures including total device-measured workplace sitting time, body mass index (BMI), self-reported health-related quality of life (Assessment of Quality of Life-8D, AQoL-8D), and absenteeism measured at 12 months. Results Compared to usual practice, the intervention was associated with greater cost (AU$431/person), benefits in terms of reduced workplace sitting time [-46.8 minutes/8-hour workday, 95% confidence interval (CI):-69.9–-23.7] and increased workplace standing time (42.2 minutes/8-hour workday, 95% CI 23.8–60.6). However, there were no significant benefits for BMI [0.148 kg/m2 (95% CI-1.407–1.703)], QoL-8D [-0.006 (95% CI-0.074–0.063)] and absenteeism [2.12 days (95% CI-2.01–6.26)]. The incremental cost-efficacy ratios (ICER) ranged from AU$9.94 cost/minute reduction in workplace sitting time to AU$13.37/minute reduction in overall sitting time. CEA showed the intervention contributed to higher life year (LY) gains [0.01 (95% CI 0.009–0.011)], higher health-adjusted life year (HALY) gains [0.012 (95% CI 0.0105 – 0.0135)], and higher net costs [AU$344 (95% CI $331–358)], with corresponding ICER of AU$34 443/LY and AU$28 703/HALY if the intervention effects were to be sustained for five-years. CEA results were sensitive to assumptions surrounding intervention-effect decay rate and discount rate. Conclusions The intervention was cost-effective over the lifetime of the cohort when scaled up to the national workforce and provides important evidence for policy-makers and workplaces regarding allocation of resources to reduce workplace sitting.